Pengembangan Media Pembelajaran Kimia Berbasis Web pada Materi Sistem Periodik Unsur - Suryani, Mirna; Burhanuddin, Burhanuddin; Sofia, Baiq Fara Dwirani (Chemistry Education Practice, 2025)
The purpose of this study was to determine the development process, validity, and practicality of web-based chemistry learning media on the Periodic System of Elements. The type of research used is research and development (R&D) with the ADDIE development model. This ADDIE development research model consists of 5 stages, namely analysis, design, development, implementation and evaluation. Students of class XI IPA SMAN 3 MATARAM, consisting of six classes, became the population of this study. Cluster random sampling was the sampling method in this study. Cluster random sampling is sampling at the cluster/group level randomly and class XI IPA 3 was chosen as the research sample. The validity test results of the average V value of 0.77 and the average reliability level of R = 85% show that the learning media is valid and reliable. Meanwhile, student responses in the practicality test showed a positive response with an average practicality of 82.06%, so that the learning media developed was classified as very practical. Based on the results of the analysis, the learning media products developed are valid and practical to use in the teaching process.